TWO ASPECTS OF RELIGIOUS FAITH (FROM THE POINTS OF VIEW OF THOMAS AQUINAS AND WILLIAM JAMES) - Лубський, В. І.; Горбаченко, Т. Г. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article deals with the matter of faith from the points of view of Thomas Aquinas, the most famous representative of Scholasticism in XIII century, a theologian and philosopher and also of William James, an outstanding American psychologist and philosopher of XIX century, one of the grounders of pragmatism, the author of such research papers on philosophy of religion as “Will to faith” (1896) and “Variety of Religious Experience” (1902).